Pengaruh Kualitas Kehidupan Kerja terhadap Kinerja Pegawai pada Dinas Pemuda dan Olahraga Kabupaten Batanghari - Neng Setiawati; Satya Wahyudi (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2019)
This study aims to provide information related to the Quality of Work Life on Employee Performance. Quality of Work Life is a problem that can not be underestimated, because it will affect the Employee Performance in achieving organizational goals. Achievement of organizational goals tends to decline is allegedly associated with work morale that is also unstable. This research is aimed to find out how big influence of Quality of Work Life to Employee Performance at Dinas Pemuda dan Olahraga Kabupaten Batang Hari Regency either arsial or simultaneously. The method used in this study is descriptive and verifikatif with independent variables (Work Life Quality) and the dependent variable (Employee Performance). The unit of analysis of this study is all employees of the Dinas Pemuda dan Olahraga Kabupaten Batang Hari Regency, the sample in this study amounted to 38 employees, taken with the technique of withdrawal Proportional random sampling. Test data analysis using Path Analysis (Path Analysis) with the help of SPSS 20.0 for windows program. The Application of Quality of Work Life has been very well implemented, Morale looks increasing in both criteria and Employee Performance is included in the criteria very well. The results showed that the Quality of Work Life directly affects Employee Performance of 8.5%.